Effect of Financial Restructuring on Customer Satisfaction in Life Insurance Companies in Kenya (Cuea Journal of Business and Economics, 2025)
Kenya life insurance firms have had a big customer satisfaction problem as their level of customer satisfaction only reached 65 out of 80 as per the industry whilst the firm had to undertake massive financial restructuring. This study was therefore conducted to determine the impact of financial restructurings on customer satisfaction of life insurance companies in Kenya. The study was grounded on the Trade-off Theory which dealt with the interplay between the advantages of debt financing and financial distress costs in maximizing capabilities of capital structures and service delivery. The descriptive research design was utilized, and a total of 187 employees were sampled in 23 licensed composite life insurance companies through a stratified random sample. In the correlation analysis, the financial restructuring and customers' satisfaction showed a positive and significant relationship (r = 0.542, p < .01). This was confirmed by simple regression test, and there was enough support of financial restructuring as a significant predictor of customer satisfaction (0.156, p < 0.05) while 57.4% of the variance was under this model together with other predictors. This study found out that customer satisfaction of financial restructuring established a positive impact on the customers because they got stable organizations and therefore provided them with better services.